Synthetic versus analytic expressions - Acedo-Matellan, V (Wiley, 2023)
A single semantic representation can be expressed via one word, in a synthetic expression, or via multiple words, in an analytic expression. Similarly, the notions of synthetic and analytic can be related to how features are expressed in morphemes: they can be encoded either in one single morpheme or in several morphemes. Pairs of related synthetic and analytic expressions are found abundantly both within and across languages, which explains why the synthetic-analytic difference has been exploited by scholars since the XVII century to define linguistic typologies and phases of diachronic change. Within generative-transformational grammar, the synthetic-analytic connection finds a parallel in multi-stratality. All major generative models map a basically analytic representation onto one that contains some degree of syntheticity. In the latest, minimalist instantiations, different mechanisms are devised to produce a packaging of features into morphemes and of morphemes into words. Moreover, these models have produced a bunch of successful predictions about the universal constraints on the synthetic vs analytic realization of linguistic expressions.